The Relationship between Family Support and Foot Care Compliance with Recurrent Diabetic Foot Wounds - Manggasa, Dafrosia Darmi; Agusrianto, Agusrianto; Langitan, Rosamey Elleke (Poltekkes Kemenkes Semarang, 2024)
As many as 15-25% of Diabetes Mellitus (DM) patients have the potential to experience diabetic foot ulcers and the rate of recurrence or recurrence of diabetic ulcers is 50% to 70% over 5 years.Â A quarter of patients with Diabetes Mellitus have the potential to develop diabetic foot sores or diabetic ulcers and more than half to 70% have a recurrence of diabetes mellitus over 5 years. Recurrent diabetic ulcers have various impacts such as reduced quality of life, economic burden, and psychological, and social effects, even if not treated properly, they can lead to infection, amputation, and even death. The study aimed to analyze the relationship between family support and foot care compliance with the incidence of recurrent diabetic ulcers. The study design was a cross-sectional study, with a sample size of 50 diabetic ulcer patients and the family support measurement instrument was the Hensaring Diabetes Family Support Scale (HDFSS). The results of statistical analysis using the chi-square test obtained p value = 0.013. Patients who adhere to foot care experience recurrent wounds (12%) and those who do not comply with foot care experience recurrent wounds (34%). Statistical analysis using the chi-square test obtained p value = 0.039. It can be concluded that family support and compliance with foot care are related to the incidence of recurrent diabetic foot injuries, so it is recommended to comply with foot care and provide support for DM patients to prevent recurrent foot injuries.